The collins encyclopedia of military history from 3500 B.C to the Present - Dupuy, R.Ernest.; Dupuy, Trevor N. ([S.l.] : Collins, 1993)
This is a guide to the world's military history from ancient times to the present, describing not only wars and combat operations but also the parallel growth of military tactics, strategy and weaponry. Each major military event and its effect on world history is described. Containing over 22 chapters, each of which opens with an essay summarizing the miltiary highlights of the period including leaders, developments, tactical and strategic trends, this book places each major operation in its political and social perspective. A continent-by-continent assessment of wars and battles follows the background description and analysis.
Keywords: Military art and science; Military history